2015
DOI: 10.1158/2326-6066.cir-14-0184
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to the Vacuolar ATPase Complex Accessory Unit ATP6S1 in Patients with Malignant Melanoma

Abstract: The augmentation of high-titer antibodies to ATP6S1 is associated with favorable clinical outcomes in patients who received vaccination with autologous, irradiated tumor cells engineered to secrete GM-CSF and allogeneic bone marrow transplantation. Cellular immune responses to ATP6S1 are unknown. To define its role as an immune target, examination of cellular responses to ATP6S1 and immunity related to current therapies such as checkpoint blockade is needed. We used an overlapping peptide library representing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“… 6 Mutations in various subunits of the V-ATPase complex have been linked to osteopetrosis, 7 , 8 x-linked myopathy, 9 distal renal tubular acidosis, sensorineural deafness, 10 , 11 and pulmonary tuberculosis, 12 and the complex has been studied as a potential dependency of certain cancer cells. 6 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 6 Mutations in various subunits of the V-ATPase complex have been linked to osteopetrosis, 7 , 8 x-linked myopathy, 9 distal renal tubular acidosis, sensorineural deafness, 10 , 11 and pulmonary tuberculosis, 12 and the complex has been studied as a potential dependency of certain cancer cells. 6 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…6 Mutations in various subunits of the V-ATPase complex have been linked to osteopetrosis, 7,8 x-linked myopathy, 9 distal renal tubular acidosis, sensorineural deafness, 10,11 and pulmonary tuberculosis, 12 and the complex has been studied as a potential dependency of certain cancer cells. 6,13,14 Beyond its degradative function, recent studies have identified the lysosome as a critical component of various signaling pathways. For example, amino acids in the lysosomal lumen promote the recruitment of the mechanistic target of rapamycin (mTOR) to the lysosomal membrane and the activation of mTOR signaling in a V-ATPase-and ragulatordependent manner, 15,16 leading to enhancement of cell growth and protein synthesis and inhibition of autophagy.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As responses are often slow, patients may not benefit clinically when presenting with rapidly progressing clinical symptoms. Currently, there are no biomarkers to predict who may benefit from ipilimumab, hence patients can undergo treatment and some associated risk without reduction or stabilization of their disease [16][17][18][19][20]. Notably ipilimumab can be used in patients regardless of their BRAF status.…”
mentioning
confidence: 99%